Legitimacy Of The Prosecutor's Authority In Investigation On Criminal Acts Of Corruption - Sukoco, Ahmad; Darwati, Darwati (Pusat Publikasi Nusantara, 2023)
ABSTRACT Corruption is a crime that is growing in various forms. So corruption needs to be eradicated as early as possible to its roots. Institutions that have the authority can carry out their responsibilities based on a legal system approach in order to take efforts and actions to eradicate criminal acts of corruption, including the Prosecutor's Office in the form of investigations. An investigation is a series of actions by an investigator in terms of and according to the method regulated in this law to seek and collect evidence which with that evidence makes clear about the criminal act that occurred and in order to find the suspect. The Legal Basis for Prosecutors in Carrying Out Investigation Authorities Against Criminal Acts of Corruption in essence, namely: Law Number 16 of 2004 concerning the Prosecutor's Office, Law Number 31 of 1999 concerning Eradication of Corruption Crimes based on Law Number 20 of 2001 concerning Amendments to Laws -Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, and the Criminal Procedure Code. Normatively, the relationship with the prosecutor's authority is regulated by Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia. Based on Article 1 point 1 of Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia, it is stated that the Prosecutor is a functional official who is authorized to act as a public prosecutor and implementer of court decisions who have obtained legal force and other powers based on the law. In terms of exercising authority over criminal acts of corruption, based on Article 30 of Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia, the duties and authorities of the Prosecutor's Office are, among others: Paragraph 1 letter d, Conducting investigations into certain criminal acts based on the law and letter e. The application of the investigative authority carried out by the prosecutor against the perpetrators of criminal acts of corruption in the jurisdiction of the Indramayu District Attorney's Office, West Java Province. the existence of allegations of criminal acts of corruption in essence the procedures carried out in accordance with the provisions determined by the Criminal Procedure Code which are based on Article 183 and Article 184 regarding the acquisition of evidence in order to prove the existence of a criminal act. The implementation of the process is adjusted to the performance of the procedures, functions and duties of the Indramayu District Attorney's Office, including; the investigation stage is carried out by the Intelligence Unit and follow-up to the performance of the investigation, namely the investigation is carried out by the Special Crimes Unit, which then carries out efforts and actions including; summoning or requesting witness statements, collecting written evidence, requesting information from suspects and asking for expert advice.